2017
DOI: 10.1016/j.envpol.2017.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Ambient sulfur dioxide levels associated with reduced risk of initial outpatient visits for tuberculosis: A population based time series analysis

Abstract: Short-term exposure to ambient SO was associated with reduced risk of initial TB outpatient visits, suggesting acute protective effects of low-level ambient SO exposure on bacteria-induced pulmonary infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 29 publications
4
44
0
1
Order By: Relevance
“…So, Generalised additive model (GAM) with Gaussian distribution was utilised to connect the infected rate due to COVID-19 and air pollutants or meteorological parameters (Chuang et al, 2011;Gao et al, 2019;Ravindra et al, 2019;Sun et al, 2015;Tong et al, 2018;Yoon, 2019;Zhang and Batterman, 2010). The model also used to estimate the correlations between moving average concentrations of air pollutants and meteorological factors at Lag0-7, Lag0-14 and Lag0-21 with daily reported COVID-19 infected cases in India (Charles et al, 2020;Ge et al, 2017;Hao et al, 2019;Liang et al, 2020a;Lin et al, 2013;Jiandong Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…So, Generalised additive model (GAM) with Gaussian distribution was utilised to connect the infected rate due to COVID-19 and air pollutants or meteorological parameters (Chuang et al, 2011;Gao et al, 2019;Ravindra et al, 2019;Sun et al, 2015;Tong et al, 2018;Yoon, 2019;Zhang and Batterman, 2010). The model also used to estimate the correlations between moving average concentrations of air pollutants and meteorological factors at Lag0-7, Lag0-14 and Lag0-21 with daily reported COVID-19 infected cases in India (Charles et al, 2020;Ge et al, 2017;Hao et al, 2019;Liang et al, 2020a;Lin et al, 2013;Jiandong Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…study in South Korea reported that an increased concentration of SO 2 might increase the morbidity of TB in males but not in females (Hwang et al, 2014). Conversely, a study in Ningbo, China, found that exposure to SO 2 might function as a protective factor against TB (Ge et al, 2017). This counterintuitive protective effects may be attributed to the antimicrobial properties of SO 2 .…”
Section: Variablesmentioning
confidence: 95%
“…In South Korea, Hwang et al found that male TB patients were more susceptible to incremental concentrations of SO 2 than females (Hwang et al, 2014). Conversely, in a time-series analysis in Ningbo, China, Ge et al reported that ambient SO 2 exposure might be a protective factor for TB (Ge et al, 2017). However, the above studies were mostly carried out in economically developed areas.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on the effects of sulfur dioxide on tuberculosis occurrence in human populations was conducted. 138 The authors found protective effects of this gas when patients were exposed to lowlevel ambient sulfur dioxide against TB.…”
Section: Sulfur Dioxidementioning
confidence: 98%